13th International Public Communication of Science and Technology. Mayo 5 al 8, 2014, Salvador, Brasil. (2014)
The Questions Network (Red de las preguntas) is a digital project developed by The Children‟s University of EAFIT in Medellín, Colombia. This project collects questions from children and teenagers and answers them through different formats, trying to encourage curiosity, critical thinking and the sharing of knowledge. In The Questions Network, questions have an author. Every time a child leaves a question on the microsite, he/she is asked to leave his/her name, age and contact information. Each child is notified when his/her question is published and answered. The project is open to every young Spanish speaker in the world; to participate, a child needs only curiosity and Internet access. The project also looks to involve researchers from many areas, encouraging them to think about the essence of their work and to share their knowledge in a simple but rigorous way. This article presents an analysis of obtained results in the first three years of the project, as well as the found difficulties from a social perspective of the knowledge gathered and the communication of Science.